Misuse of prescription and illicit drugs among high-risk young adults in Los Angeles and New York - Stephen E. Lankenau; Sheree M. Schrager; Karol Silva; Alex Kecojevic; Jennifer Jackson Bloom; Carolyn Wong; Ellen Iverson (SAGE Publishing, 2012)
Background. Prescription drug misuse among young adults is increasingly viewed as a public health concern, yet most research has focused on student populations and excluded high-risk groups. Furthermore, research on populations who report recent prescription drug misuse is limited. This study examined patterns of prescription drug misuse among high-risk young adults in Los Angeles (LA) and New York (NY), which represent different local markets for illicit and prescription drugs. Design and Methods. Between 2009 and 2011, 596 young adults (16 to 25 years old) who had misused prescription drugs within the past 90 days were interviewed in Los Angeles and New York. Sampling was stratified to enroll three groups of high-risk young adults: injection drug users (IDUs); homeless persons; and polydrug users. Results. In both sites, lifetime history of receiving a prescription for an opioid, tranquilizer, or stimulant was high and commonly preceded misuse. Moreover, initiation of opioids occurred before heroin and initiation of prescription stimulants happened prior to illicit stimulants. NY participants more frequently misused oxycodone, heroin, and cocaine, and LA participants more frequently misused codeine, marijuana, and methamphetamine. Combining prescription and illicit drugs during drug using events was commonly reported in both sites. Opioids and tranquilizers were used as substitutes for other drugs, e.g., heroin, when these drugs were not available. Conclusion. Patterns of drug use among high-risk young adults in Los Angeles and New York appear to be linked to differences in local markets in each city for illicit drugs and diverted prescription drugs.